Proposta de metodologia experimental para a análise e quantificação da emissão de metano com aplicação na produção de carvão vegetal em laboratório - Maia, Ivana Márcia Oliveira (2014)
Carbon credits have been created to assist the process of mitigation of Greenhouse Gases (GHG) and carbon sequestration. The carbon credits objective is to stimulate the implantation of projects focused in the emission reduction or capture of those gases. As a signatory of Kyoto Protocol, Brazil does not have any reduction targets to meet. However, its needs to keep United Nations (UN) aware of its level of carbon emissions, seeking the development of strategies focused on climate changes. Thereby, it is part of the group of countries that can negotiate their reductions with more pollutant countries. Global pioneer in the use of charcoal for the production of pig iron, Brazil has this energy input as relevant production for the Brazilian economy, although some traditional processes are related to social an environmental problems. This thesis proposes an experimental methodology for the quantification of methane applied to vegetable charcoal production in laboratory. Thus, based on the estimation of the amount of methane emitted in the carbonization process improvements can be deployed in productive method for improvement of product, process and certified emission reduction gases into the atmosphere.